Performance of Dairy Factory Wastewater Treatment Plant (Case Study of Pasuruan Dairy Factory East Java) - Alfiah, Taty; Pertiwi, Diandra Dieva (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
The 'ILP' company produces bottled milk with chocolate, melon, strawberry, and vanilla flavors in colorless HDPE (High-Density Polyethylene) plastic bottles and aluminum foil covers. The 'ILP' dairy industry wastewater treatment process stages include bar screen, grease trap, equalization tank, flocculation-coagulation, primary clarifier, aeration tank/activated sludge, and secondary clarifier. The research aims to determine the performance of the dairy factory's WWTP (Wastewater Treatment Plant) in terms of TSS (Total Suspended Solids) and COD (Chemical Oxygen Demand) parameters. This field-scale research was carried out for approximately 5 weeks (35 days) at the wastewater treatment plant of the ILP company. Wastewater sampling is carried out at the inlet point, equalization tank, primary sedimentation, aeration tank, and outlet point of WWTP. Wastewater examination conducted in the company's internal laboratory, including temperature, pH, total suspended solids (TSS), and chemical oxygen demand (COD). The dairy factory WWTP (wastewater treatment plant) can generate TSS (total suspended solids) effluent of 22 mg/L and COD (chemical oxygen demand) of 26.8 mg/L to meet the applicable wastewater quality standards. The treatment efficiency of the dairy industry WWTP for TSS is 94.7% and COD is 98.1%.